Methodologies for the Accelerated Aging Test in Triticale Seeds - Castellanos, César Iván Suárez; Lemes, Elisa Souza; Almeida, Andréia da Silva; Meneghello, Geri Eduardo; Tunes, Lilian Madruga de (Agrociencia Uruguay, 2018)
Triticale is a Poaceae widely used in the southeastern region of Brazil in the winter period. However, the seeds of this species may have low vigor as consequence of exposure to adverse factors, either biotic or abiotic, during their formation. This means that the evaluation of the vigor is essential to estimate the physiological potential of the seed lots destined to the cultivation of this forage. The objective of this work was to evaluate the methodology of the accelerated aging test to determine the physiological potential of triticale seeds. We determined the percentage of moisture, percentage and seedling emergence speed, and percent germination before and after accelerated aging, which was performed using water, saturated saline solution, and unsaturated saline solution for 48, 72 and 96 hours at 42 ° C. The interpretation of the results allowed us to conclude that the accelerated aging test for 48 hours with saline solution, saturated or not, is efficient to evaluate the vigor of triticale seeds.